Motivation and Self – Confidence and their relation to Routine Performance on Parallel Bars in Men’s Artistic Performance - Hamza, Mohammed; Sekran, Jamal; Abdullah, Ahmed (Journal of Physical Education, 2021)
The research aimed at identifying the relationship between motivation and self–confidence on the performing routines in the parallel bar. The researchers used the descriptive method on (480) thirds year college of physical education and sport sciences/ university of Baghdad students. The data was collected and treated using proper statistical operations to conclude that there is a high correlation relationship between motivation and self-confidence with routine performance on parallel bars. In addition to that, the researchers concluded that third-year students have high motivation and self – confidence and there is a positive relationship between motivation, self-confidence, and routine performance on parallel bars.